Warm Compress Therapy With Essential Oil Aroma For Pain In Pregnant Patients After Caesarean Section - Treasa, Adisty Dwi; Arnianti, Arnianti; Mayasari, Rini; Qudratullah, Fyzria; Rahmawati, Agustini Liviana Dwi; Ula, Zumrotul; Nurmiati, Nurmiati; Hardiyanti, Sitti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Warm compresses in addition to reducing the sensation of pain can also increase the healing process of damaged tissue. The use of heat in addition to providing the effect of overcoming or eliminating the sensation of pain, this technique also provides physiological reactions including increasing the inflammatory response, increasing blood flow in the tissue and increasing edema formation. The purpose of this study was to determine the effect of warm compress therapy with jasmine essential oil aroma on reducing pain intensity in post-Cesarean patients at Makassar Hospital. This type of research is quantitative research, with a pre-experimental research method using a one group pre-test - post-test design. The results of the univariate analysis obtained the pain intensity of post-Cesarean patients before warm compresses with aroma and respondents experienced moderate pain. While the pain intensity of post-Cesarean patients after warm compresses experienced mild pain. The conclusion shows that there is an effect of warm compress therapy with essential oils on reducing pain intensity in post-Cesarean patients at Makassar Hospital.